Menghitung Diameter Mare Bulan dengan Menggunakan Teleskop dan Kamera CCD - singgih prana putra (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2021)
The moon is the only natural satellite of the earth in space that has many variety of surface profiles. These profiles are Crater and Maria. Lunar maria and craters vary widely in size from small to large. This journal aims to measure the diameter of the lunar mare using a comparison of the pixel values of the image and laptop screen as well as the specifications of the refractor telescope and CCD camera. This method also aims to be used with or without a telescope like using only DSLR cameras. The Maria that we measured its diameter were Nectaris, Serenitatis, Tranquilitatis and Vaporum. These Maria are close to the center of the lunar circle to avoid the darkening effect. The diameters of the mare Nectaris, Serenitatis, Tranquilitatis and Vaporum are 380.5 km, 651.5 km, 439.9 km and 323.1 km, respectively, with an error range of 3.38 49.77 %.